Effect of the Energy Transition on Food Security : The Role of the Female Agricultural Workforce in WAEMU Countries - Angbonon Eugene Kamalan; Assande Pierre Kadjo; Kouakou Romaric Kouame (European Scientific Journal, ESJ, 2025)
This article looks at the problem of food insecurity and nutrition in Africa. The study analyses the role of women in the relationship between the energy transition and food security in the 8 WAEMU countries over the period 1996-2022. The use of an ARDL model shows that the energy transition significantly and symmetrically improves food security in the short term, but has a negative and asymmetric effect in the long term. The interaction between the energy transition and the female agricultural workforce has a positive effect in the long term, but is neutral in the short term. We recommend that, in order to ensure sustainable food security, the involvement of women in the agricultural sector must be strengthened. Public policies and private initiatives must therefore promote women's access to sustainable energy resources, while supporting their role in innovation and the management of agricultural practices.